In silico analysis of transcriptional initiation frequency of plant genes - ZHANG Yang; XU Guo-hua; FAN Long-jiang (浙江大学学报. 农业与生命科学版)
Transcriptional initiation frequency of 17,437 genes from 7 plants was estimated based on data of UniGene database using bioinformatics method. The results indicated that average distance of transcriptional initiation of plant genes was 171 bp (at mRNA level) or 174 bp (at genomic DNA level) and distribution of their transcriptional initiation frequencies presented a normal distribution in general. A pipeline program, PIFMaker and a database, PIFdb (Potential transcriptional initiation frequency database), were developed in this study. The data of Release 2.0 of PIFdb database was used in this analysis.